Pelatihan Power Point Kreatif berbasis Animasi Pada Guru-guru SMP Swasta Wiyata Dharma - Kristian Telaumbanua; Florida Damanik; Heru Kurniawan (Prosiding SISFOTEK, 2021)
This training aims to provide teachers with an understanding of the usefulness of the various features found in the Microsoft PowerPoint application and how to use them to create a more interesting learning environment by using various animations during presentations/teaching. The animation that appears in a presentation is expected to make the presenter/teacher still get the attention of the listeners/students and students and reduce the level of boredom that arises due to the presentation slide containing too much text. The training provided has a level of complexity and difficulty that is adjusted to the current conditions of understanding of the teachers through a short survey conducted at the beginning of the training where teachers will be asked to provide an overview of knowledge about Microsoft PowerPoint in a form. After that the training team will carry out training exercises from the training that will be given to the teachers and separate several training sessions to follow the progress of the results of the teachers. The results of the training can be seen directly from the results of simple animations made by the teachers independently according to the instructions of the trainers. The results obtained during the training can later be used in making teaching and learning process modules or even presentation slides for non-academic needs such as introducing products, elaborating structures, showing a simple understanding of a process and so on.